2017
DOI: 10.1037/spq0000202
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an interdependent group contingency on the transition behavior of middle school students with emotional and behavioral disorders.

Abstract: An ABAB design was used to evaluate the effectiveness of an interdependent group contingency with randomized components to improve the transition behavior of middle school students identified with emotional and behavioral disorders (EBDs) served in an alternative educational setting. The intervention was implemented by one teacher with three classes of students, and the dependent variable was the percentage of students ready to begin class at the appropriate time. Data revealed significant improvements in stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…Thus, the current study’s results contribute to our understanding of optimal response to intervention for SCI-A, as well as a better understanding of under what conditions (i.e., more antiosical behavior) modified dosage and intensity of the intervention may be necessary. The fields of special education and school psychology have recognized the importance of ecological validity and understanding real-world conditions, and, as such, the group-level moderators explored in the current article are based in part on data sources that are accessible and consistently used by school personnel (Hawkins et al, 2017; Stage et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the current study’s results contribute to our understanding of optimal response to intervention for SCI-A, as well as a better understanding of under what conditions (i.e., more antiosical behavior) modified dosage and intensity of the intervention may be necessary. The fields of special education and school psychology have recognized the importance of ecological validity and understanding real-world conditions, and, as such, the group-level moderators explored in the current article are based in part on data sources that are accessible and consistently used by school personnel (Hawkins et al, 2017; Stage et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Schools used clinical diagnosis provided by outside clinicians as part of the data by which to make programming decisions. As such, upon referral to the project and consistent with other research of this nature (Hawkins et al, 2017; McDonald et al, 2016; Stage et al, 2008) schools provided records of any clinical diagnosis for each student. Diagnoses are reported here if they were provided by an external medical or psychological professional (i.e., category of special education eligibility did not count as a diagnosis).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several research studies have documented the positive effects of all types of group contingencies for supporting students with EBD (Groves & Austin, 2017;Hansen & Lignugaris-Kraft, 2005;Hawkins et al, 2017). Studies have shown that group contingencies can reduce disruptive behavior in students with EBD, which is particularly important given the specific needs of this population (Theodore et al, 2001(Theodore et al, , 2004.…”
Section: Group Contingenciesmentioning
confidence: 99%
“…Therefore, the current study aims to integrate the theory of planned behavior (TPB), which concerns motivation and capability factors, and signaling theory, which concerns the information quality of ECAs, to shed light on this neglected mechanism. We further investigate this mechanism under the contingencies of students' demographic profiles, such as their gender, their year in school, and whether they have a part-time job, which have been proven to have an impact on people's behavior (Hawkins et al, 2017;Maggin et al, 2017). The current article, therefore, incorporates these variables as moderators to capture and clarify a holistic picture.…”
Section: Introductionmentioning
confidence: 99%